2013
DOI: 10.1002/adma.201302459
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Hierarchical Mesoporous/Macroporous Carbon: A High‐Performance Catalyst for Rechargeable Li–O2 Batteries

Abstract: Three-dimensional ordered mesoporous/macroporous carbon sphere arrays (MMCSAs) are synthesized and then used as a catalyst for Li-O2 batteries. The hierarchical porous structure of the MMCSAs not only facilitates electrolyte immersion and Li(+) diffusion but also provides an effective space for O2 diffusion and O2 /Li2 O2 conversion, and thus efficiently improves the performance of Li-O2 batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
185
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(188 citation statements)
references
References 32 publications
3
185
0
Order By: Relevance
“…So far, great efforts have been devoted to developing the cathode catalyst with high activity and stability for oxygen-involved reactions in Li-O2 batteries [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Peng et al [7] firstly reported the rechargeable Li-O2 batteries by catalyzing the reversible formation/decomposition of the Li2O2 on porous Au catalyst, which makes Li-O2 batteries promising for practical use.…”
Section: Introductionmentioning
confidence: 99%
“…So far, great efforts have been devoted to developing the cathode catalyst with high activity and stability for oxygen-involved reactions in Li-O2 batteries [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Peng et al [7] firstly reported the rechargeable Li-O2 batteries by catalyzing the reversible formation/decomposition of the Li2O2 on porous Au catalyst, which makes Li-O2 batteries promising for practical use.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, catalysts have been utilized to reduce the overpotentials and to increase the cycle life. Potential catalysts such as metals, metal oxides, perovskite, carbon nanotubes, graphene, and organic compounds have been investigated 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24. Ruthenium metal has recently demonstrated superior capability to reduce charge overpotential during the oxygen evolution reaction (OER) over other catalysts 25.…”
mentioning
confidence: 99%
“…Designed hierarchical porous architectures with macropores surrounded by ordered mesoporous channels can provide enough space for O 2 diffusion and O 2 /Li 2 O 2 conversion, leading to perfect cycling performance (Fig. 5d) [23].…”
Section: Defect and Pore Controlled Carbon Nanostructures For Li-airmentioning
confidence: 99%
“…Because ORR, OER, and HER have been reviewed in several previously published articles [4,[10][11][12], the focus in this review will be on recent advances and new reactions (e.g., CO 2 RR, multifunctional electrocatalysis). A critical overview of efficient methods for developing carbon-based metal-free catalysts for various energy conversion/storage and environmental protection devices, including ORR in fuel cells [13][14][15][16][17], ORR and OER in metal-air batteries [18][19][20][21][22][23][24][25][26][27][28], OER and HER in water-splitting units [29][30][31], I − /I 3− reduction in dye-sensitized solar cells [32][33][34][35], and CO 2 RR in Li-CO 2 batteries [36][37][38][39][40][41][42] will then be provided. Finally, perspectives and challenges in this fast-growing and significant field are outlined.…”
Section: Introductionmentioning
confidence: 99%